OPTIMAL WORK-REST SCHEDULE FOR COMPUTER USERS (International Journal of Physiotherapy, 2017)
Background: Musculoskeletal disorders are the most common health problems for computer users who work for an extended period. The aim of this study was to identify the best work-rest schedule with the three different work-rest groups: no rest break, mid-rest break, and multiple- rest breaks, which was associated with the least EMG activities of the upper trapezius muscle and would be beneficial for musculoskeletal health.Methods: Forty-five right-handed females complaining of neck discomfort were randomly assigned into three equal groups, Group1 (no rest break) they were be engaged in sixty minutes of typing followed by ten minutes break (60-10), group 2 (mid-rest break) thirty minutes of typing followed by five minutes break (30-5), and group 3 (multiple rest breaks) fifteen minutes of typing followed by 2.5 minutes break (15-2.5). Surface EMG was used to pick up the electrical activity of right and left upper trapezius throughout the computer typing task.Results: There was a statistically significant reduction of normalized RMS (p